Arrangement of Marriage Agreements Outside of Marital Treasure in Keeping the Household - Sekar Ayu Garindya; Arsin Lukman (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
A concrete law is needed to protect and guarantee the rights and obligations of husbands, wives, and children in fostering a household. Because it regulates agreements related to treasure matters and other important matters, this concrete law aims to achieve the purpose of marriage under the applicable laws and regulations, such as a marriage agreement. Many people are unaware that the marriage agreement regulates marital treasure and outside treasure if both parties agree and it does not conflict with the law, morality, or public order.